Towards stable lithium-sulfur battery cathodes by combining physical and chemical confinement of polysulfides in core-shell structured nitrogen-doped carbons. (May 2020) - Yan, Runyu; Oschatz, Martin; Wu, Feixiang
Abstract: Despite intensive research on porous carbon materials as hosts for sulfur in lithium-sulfur battery cathodes, it remains a problem to restrain the soluble lithium polysulfide intermediates for a long-term cycling stability without the use of metallic or metal-containing species. Here, we report the synthesis of nitrogen-doped carbon materials with hierarchical pore architecture and a core-shell-type particle design including an ordered mesoporous carbon core and a polar microporous carbon shell. The initial discharge capacity with a sulfur loading up to 72 wt% reaches over 900 mA h gsulfur −1 at a rate of C/2. Cycling performance measured at C/2 indicates ∼90% capacity retention over 250 cycles. In comparison to other carbon hosts, this architecture not only provides sufficient space for a high sulfur loading induced by the high-pore-volume particle core, but also enables a dual effect of physical and chemical confinement of the polysulfides to stabilize the cycle life by adsorbing the soluble intermediates in the polar microporous shell. This work elucidates a design principle for carbonaceous hosts that is capable to provide simultaneous physical-chemical confinement. This is necessary to overcome the shuttle effect towards stable lithium-sulfur battery cathodes, in the absence of additional membranes or inactive metal-based anchoring materials. Graphical abstract: Image 1